Influence of body position on dolphin kick kinematics - Alves, F.; Lopes, P.; Veloso, A.; Martins-Silva, A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
In backstroke, butterfly and front crawl competitive swimming underwater glide after the starts and turns is followed by a series of dolphin kicks while the body is still completely submerged. The aim of this study was to analyze the kinematics of dolphin kick in three body positions, prone, dorsal and lateral. Six national level junior swimmers (17.02 ± 0.36 years) were filmed underwater after jumping from the start blocks in order to analyze 2 complete kick cycles at maximal velocity in each position (APAS). Lateral kicking showed lower frequency and higher feet, hip, elbow and hand transverse amplitude. Swimmers used higher ankle extension in the dorsal kick. Strouhal number (dorsal: 0.95±1.31; prone: 0.86±0.07; lateral: 0.95±0.83) were within the range of previous results for subelite swimmers but failed to discriminate body positions.